Analisis Penjualan, Biaya Operasional dan Laba Bersih Pada Perusahaan Property dan Real Estate Periode 2021 - 2024 - Hieronimus Erwin Indrawan; Nazwa Adhisty Putri; Amalia Tresna Fadhilah; Intan Kusuma Dewi; Indra Prana (ARBITRASE: Journal of Economics and Accounting, 2026)
The financial performance of a Company can be seen through the analysis of Financial Statements. Income, Expenses and Profit are three interrelated accounts, where changes in income and expenses will affect the Company's profits. This research aims to analyze the company's financial statements for the 2022-2024 period to determine the Company's financial condition and performance. The analysis is focused on revenue, operating expenses, and net profit with the aim of identifying an increase or decrease from year to year. The research method used is quantitative descriptive with secondary data sources, while the data collection technique is carried out through interviews, observations, and documentation. The analysis was carried out using the Horizontal Trend method. The results of the study show that the Company experienced significant fluctuations in revenue, net profit, and operating expenses during the 2022-2024 period. A large surge in operating costs in 2024 of 506% affected the Company's financial performance but still led to an increase in net profit above 100%. The evaluation of the company's financial performance for the 2022-2022 period shows a slightly poor financial situation, because the profit generated tends to go up and down, in 2023 it will decrease by 4.75% and increase again by 85% in the following year as well as the revenue generated tends to decrease. The Company's financial performance tends to experience an increase in revenue and net profit, despite fluctuations in operating costs. The increase in operational costs is so high that it can be caused by economic conditions starting to rise after the covid pandemic. A large expense needs to be made to increase sales. The increase was mainly due to increased revenue from property sales and rental transactions managed by the Company which has branches in Jakarta and West Java.